Autologous tooth bone graft block compared with advanced platelet-rich fibrin in alveolar ridge preservation: A clinico-radiographic study - Triveni Mavinakote Gowda; Manjunath Jayashri; Usha Govindaroy Venkatesh; Rucha Shah; Amanna Baron Tarun Kumar; Manjunath Deepthi; Saloni Priya (Wolters Kluwer Medknow Publications, 2023)
Objectives: To determine the clinico-radiographic efficiency of partially demineralized dentin matrix block (PDDM block), a mixture of PDDM with advanced-platelet-rich fibrin+ (A-PRF+) and injectable platelet-rich fibrin versus A-PRF+ alone in alveolar socket preservation. Materials and Methods: Sixteen molar teeth indicated for extraction were randomly assigned into two groups. For the test group, sockets were packed with PDDM block and control group, with A-PRF+ plug alone. Clinical and radiographic cone-beam computed tomography methods were used to assess the horizontal and vertical ridge dimensional changes at baseline and 4 months. Results: Clinically, the mid buccal and palatal crestal height (10.25 ± 0.86 and 9.75 ± 0.28 mm) and alveolar ridge width (11.37 ± 0.25 mm) were significantly higher in the test group as compared to the control group, 4 months after tooth extraction (P < 0.01). Radiographically, there was improved apposition and nonsignificant resorption for the test group in ridge height and width, whereas statistically significant higher resorption was seen in the control group at 4 months. Conclusion: The application of the PDDM block demonstrated efficacy in maintaining the dimensions of the extraction socket when compared to A-PRF+ alone. This autologous and immune-free regenerative biomaterial is widely obtainable, offering a glimpse into the potential of next-generation biofuels for regeneration.